Pendidikan Islam Berwawasan Multikultural - Alam, Masnur; Daflizar, Daflizar (Sekolah Tinggi agama Islam Negeri (STAIN) Curup, 2018)
Which is prone to cause conflict, thus State Islamic Institute of Kerincias one of the stateuniversities feels obliged to include multicultural courses into its curriculum.The purpose of this study was to know the implementation of